DIFUSI INOVASI PROGRAM KELOMPOK TANI HUTAN DI KABUPATEN BENGKALIS - Resinta, Resinta (Inovasi Pembangunan : Jurnal Kelitbangan, 2024)
The Forest Farmers Group exists as an innovation with the aim of empowering the community through the conservation of biological natural resources. The presence of forest farmer groups and the active role of change agents in implementing programs to the community as a development effort can change the order of community life through social change. This research uses the theory of diffusion of innovation by Everret M. Roger. This research aims to analyze innovation, communication channels, time period, and social systems. This research used a qualitative descriptive approach, using purposive techniques with 11 informants. Data collection techniques through observation, interviews and documentation. The results of the research show that the innovation of forest farmer groups improves the order of life in society for the better with the characteristics of innovation, namely coordinated administration in government, there is training and mentoring, marketing assistance, and there is monitoring and evaluation. Forest farmer group innovations are diffused through interpersonal communication channels and social media Instagram and WhatsApp. The period of diffusion of forest farmer groups started from 2013 until now. The social systems that play a role and are involved are Forest Management Units, initiators, Non-Governmental Organizations, Village, Regency, Provincial Governments and especially farmers consisting of early adopters, early majority and late majority.